University Students' Satisfaction with their Academic Studies: Personality and Motivation Matter - Wach, F.-Sophie; Karbach, Julia; Ruffing, Stephanie; Brünken, Roland; Spinath, Frank M. (Frontiers in Psychology, 2016)
Although there is consensus about the importance of students' satisfaction with their academic studies as one facet of academic success, little is known about the determinants of this significant outcome variable. Past research rarely investigated the predictive power of multiple predictors simultaneously. Hence, we examined how demographic variables, personality, cognitive and achievement-related variables (intelligence, academic achievement), as well as various motivational constructs were associated with three different dimensions of satisfaction (satisfaction with study content, satisfaction with the conditions of the academic program, satisfaction with the ability to cope with academic stress) assessed approximately 2 years apart. Analyzing data of a sample of university students (N = 620; Mage = 20.77; SDage = 3.22) using structural equation modeling, our results underline the significance of personality and motivational variables: Neuroticism predicted satisfaction with academic studies, but its relevance varied between outcome dimensions. Regarding the predictive validity of motivational variables, the initial motivation for enrolling in a particular major was correlated with two dimensions of subsequent satisfaction with academic studies. In contrast, the predictive value of cognitive and achievement-related variables was relatively low, with academic achievement only related to satisfaction with the conditions of the academic program after controlling for the prior satisfaction level.